(untitled) (Journal of Teleological Science, 2024)
The most complex being, man, is defined by an understanding of his dignity. Nothing is more important to humanity than ensuring that dignity is respected. It is dignity that makes man ’truly human’, allowing him to manifest himself in complete freedom and express, unhindered, all the capacities and abilities with which he has been endowed or which he has developed. This paper explores various trends in the definition of human dignity and personality, while also examining the concerns of both ancient Greco-Roman and contemporary societies regarding the implementation of guarantees for human dignity in the social sphere, legal system, and interpersonal relationships. Although the exploration is limited, it aims to keep the concept of respect for human dignity at the forefront. This focus is essential, as the world can only be envisioned as a better place when human dignity is respected.